Women’s Struggle in Brian Khrisna’s Sisi Tergelap Surga: A Feminist Perspective on Indonesian Urban Patriarchy - Aditya Reza Malvino; Aditya Putra; Abiri Sabil Khaira; Firman Pangeran Lubis; Purwarno Purwarno (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2026)
This study examines the representation of women and the dynamics of patriarchal oppression in Sisi Tergelap Surga by Brian Khrisna through the lens of feminist literary criticism. It seeks to uncover how female characters experience, negotiate, and resist oppressive structures, while also exploring how the narrative constructs forms of feminist agency. Employing a qualitative textual analysis, the study identifies three dominant manifestations of oppression: patriarchal control embedded in family institutions, emotional and psychological violence, and structural marginalization shaped by the intersection of gender and socio-economic disadvantage. The findings reveal that patriarchy operates not merely as an individual attitude but as a systemic force reproduced across domestic and social domains, limiting women’s autonomy, silencing their voices, and eroding their sense of self-worth. Nevertheless, the novel does not position women solely as passive victims. Instead, it foregrounds their inner struggles, critical awareness, and gradual processes of resistance and identity reconstruction. Through narrative strategies that center women’s voices and lived experiences, the text opens a space for reclaiming agency. Ultimately, Sisi Tergelap Surga functions both as a documentation of gendered suffering and as a subtle yet powerful feminist intervention that challenges patriarchal norms and reimagines women’s positions within society. ABSTRACT INDONESIANPenelitian ini mengkaji representasi perempuan serta dinamika penindasan patriarkal dalam novel Sisi Tergelap Surga karya Brian Khrisna dengan menggunakan pendekatan kritik sastra feminis. Tujuan penelitian ini adalah untuk mengungkap bagaimana tokoh-tokoh perempuan mengalami, menegosiasikan, dan melawan struktur-struktur represif, sekaligus menelaah bagaimana narasi membangun bentuk-bentuk agensi feminis. Dengan menggunakan analisis tekstual kualitatif, penelitian ini mengidentifikasi tiga bentuk utama penindasan, yaitu dominasi patriarki dalam institusi keluarga, kekerasan emosional dan psikologis, serta marginalisasi struktural yang dibentuk oleh persilangan antara gender dan kondisi sosial-ekonomi. Hasil penelitian menunjukkan bahwa patriarki tidak hanya beroperasi sebagai sikap individual, melainkan sebagai sistem yang terlembagakan dalam ranah domestik maupun sosial, yang membatasi otonomi perempuan, membungkam suara mereka, serta mereduksi nilai diri. Namun demikian, novel ini tidak semata-mata merepresentasikan perempuan sebagai korban pasif. Sebaliknya, narasi menyoroti pergulatan batin, kesadaran kritis, serta proses bertahap dalam membangun resistensi dan rekonstruksi identitas. Dengan strategi naratif yang memusatkan pengalaman dan suara perempuan, teks ini membuka ruang bagi pemulihan agensi. Pada akhirnya, Sisi Tergelap Surga tidak hanya mendokumentasikan penderitaan perempuan, tetapi juga menghadirkan kritik feminis yang kuat sekaligus menawarkan imajinasi baru tentang posisi perempuan dalam masyarakat patriarkal.